ANALISIS ANGKA LEMPENG TOTAL BAKTERI PETIS KUPANG PUTIH (Corbula faba) INDUSTRI RUMAH TANGGA DI DESA SUNGIKULON KECAMATAN POHJENTREK KABUPATEN PASURUAN - Ikerismawati, Senja; Sholiha, Illiyatus; Yahya, Slamet (LP4MK STKIP PGRI Lubuklinggau, 2023)
White mussel (Corbula faba) is one of the fishery products belonging to the shellfish group. White mussel can be used as processed food. White mussel petis is a processed food that comes from the utilization of leftover boiled white clams mixed with granulated sugar and brown sugar and then boiled until thickened. This study aimed to analyze total plate count bacteria in the home industry for making white mussel paste in Sungikulon village, Pohjentrek, Pasuruan. This study used the total plate count method pouring technique. Analysis total plate count carried out at the Surabaya Health Laboratory Center, by testing six samples of white mussel petis and three repetitions, test data total plate count white mussel petis will be compared with SNI 2718.1:2013 to determine the quality of the sample.The results of this study indicate that the two samples do not meet the SNI 2718.1: 2013 standard, namely the SK1 sample is 82 x 103 and the SK6 sample is 22.9 x 103.. There are four samples whose values ​​are lower than SNI 2718.1: 2013, namely the SK4 sample of 0.01 x 103. SK2 sample of 0.05 x 103. Sample SK3 is 0,11 x 103 and SK5 sample is 0.42 x 103. This means that the quality of the four samples is good.